THE REALIZATION OF IDEATIONAL MEANINGS IN THE STUDENTS' RECOUNTS - Sri Mulatsih (Celt: A Journal of Culture, English Language Teaching & Literature, 2007)
English Department Students of Faculty of Languages and Letters of Dian Nuswantoro University usually have difficulties in writing English Texts. Those difficulties deal with the way to organize ideational meaning in their texts. Based on that fact. this study was conducted to know the realization of ideational meaning in the students' texts. especially recounts. The data were taken from the students' recounts and for the sake of this study. 10 recounts were chosen as the data to analyze the data. Halliday and Matthiessen 's framework (1999) was applied to get a deep understanding of Ideational Meaning. The result shows that in organizing the Ideational Meanings in their recounts. the students used sequences figures. the elements of figures: Process. Participant, and Circumstances; and the realization of those elements in lexicogrammar. Kinds of sequences (clause complexes) the student mostly made in their recount are enhancement, and extension Elaboration, locution or idea have lower portion compared to the two sequences mentioned above. Four kinds offigures arefound in the students recounts. Those are figure of doing (material and behavioral processes), figure of sensing (mental process). figure of saying (verbal process), and figure of being (relational: attributive. identifying) process. and existential process). Among the four figures mentioned above, figures of doing (material processes) with actor and goal as the key participants dominate in all texts. 112 circumstances (circumstances of time, place. manner, matter, and circumstances are realized in simple and macro circumstances. The number of macro circumstances is higher than that of simple ones. Sincepersonal recount is a text telling someone's past experience, the realization of participants in their recounts are mostly conscious simple things. Simple qualities only exist in relational (attributive) process. The processes are mostly realized in polar non- phrasal verbs in past tense. accompaniment) are found in the students' recounts. Those